2017
DOI: 10.1021/acs.langmuir.7b03307
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressurization of Lung Surfactant Microbubbles: Observation of a Strain-Rate Dependent Elasticity

Abstract: The microbubble offers a unique platform to study lung surfactant mechanics at physiologically relevant geometry and length scale. In this study, we compared the response of microbubbles (∼15 μm initial radius) coated with pure dipalmitoyl-phosphatidylcholine (DPPC) versus naturally derived lung surfactant (SURVANTA) when subjected to linearly increasing hydrostatic pressure at different rates (0.5-2.3 kPa/s) at room temperature. The microbubbles contained perfluorobutane gas and were submerged in buffered sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The length of the PEG chain, the length of the primary lipid molecules, temperature, microbubble production method, resting time after synthesis, and phase behavior and microstructure formation of the lipids in the coating may all play a role. [59][60][61] Furthermore, acoustically driven selective loss of shell components may influence shell stiffness. In our previous work, it was shown that the shell elasticity of monodisperse microbubbles formed by flow-focusing and coated by a very similar lipid mixture (DPPC:DPPA:DPPE-PEG5k, 8:1:1 molar ratio) can increase from 0.8 N/m to 2.5 N/m during multiple acoustic insonations 28 which, in part, can now be explained from a slight (2%) decrease in bubble radius due to acoustically driven dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…The length of the PEG chain, the length of the primary lipid molecules, temperature, microbubble production method, resting time after synthesis, and phase behavior and microstructure formation of the lipids in the coating may all play a role. [59][60][61] Furthermore, acoustically driven selective loss of shell components may influence shell stiffness. In our previous work, it was shown that the shell elasticity of monodisperse microbubbles formed by flow-focusing and coated by a very similar lipid mixture (DPPC:DPPA:DPPE-PEG5k, 8:1:1 molar ratio) can increase from 0.8 N/m to 2.5 N/m during multiple acoustic insonations 28 which, in part, can now be explained from a slight (2%) decrease in bubble radius due to acoustically driven dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Control microbubbles were made with the pure lipid component 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) (Avanti Polar Lipids, Alabaster, AL), as previously described [15]. DPPC was weighed and dissolved in chloroform (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Beractant has been shown to stabilize microbubbles by forming a monolayer at the gas/water interface with attached bilayer folds that extend into the aqueous phase [14]. The Beractant film is transported from the monolayer to the bilayer folds during hydrostatic compression of the microbubble [15]. These attached bilayer folds may serve as a film reservoir for the expanding interface.…”
Section: Introductionmentioning
confidence: 99%
“…While these forces ultimately ensure complete bubble dissolution, the rate is hindered by the limited permeability [59] and elasticity [60] of the shell, thereby allowing sufficient stability for an imaging exam. Coated microbubbles dissolve according to a modified Epstein-Plesset relation [61]: dRdt=H[1F+Λ/Rρ1+2Λ/3Rρ][1Ωw+Ωshell] Λ=2MBT(γ0+Eβ)…”
Section: Properties Of the Ucamentioning
confidence: 99%
“…a) Uncoated microbubbles containing various gases in a saturated medium dissolving due to surface tension; gas parameters taken from [60]. B) Lipid-coated vs. uncoated air bubbles dissolving in an undersaturated medium ( F = 0.8); lipid shell permeability is taken from [64] and elasticity is taken from [61].…”
Section: Figurementioning
confidence: 99%